Przemiany ekonomicznej struktury rolnictwa w krajach Europy Zachodniej - Babiak, Jerzy (Wydział Prawa i Administracji UAM, 1983)
A process of concentration of production became the most conspicious effect of the structurai changes in the Western European States. In spite of the poist- -World War Two progress the level of concentration in agriculture is still much lower than tin other branches of production. The following can be mentioned among the main reason of that state of things: historical conditions of the development of agriculture, distinctive features of the production process in agriculture, developed system of the so called vertical integration. Two period's can be distinguished in a course of concentration after the war, The first one dating back to the end on the war and lasting to the sixties, and the second one lasting from the beginning of sixties to our decade. A lower rate of concentration was characteristic of the first period while the second one brought about accelerated dynamic transformations of quantity and structure of productive units in agriculture. In the result, there is a decline in total amount of farms, growth of an average farm's area and an increase in the portion of medium and large units in a structure of farms. Transformations of the agrarian structure are closely interrelated with changes of the labor resources in agriculture. A general decline in these resources in favor of other branches can be observed. The second trend is a fall in hired labor and a large bi-occupational population. Structural transformations in agriculture are not effected only by self-feeding market processes. Much influence is yielded by policies of particular governments and by a Common Market policy, especially in the recent years.
Transformations of the economic structure of agriculture in the Western European states